PENINGKATAN KEMAMPUAN MENULIS PUISI DENGAN METODE PICTURE AND PICTURE PADA SISWA KELAS V SDN 1 SUKAMENANTI BANDAR LAMPUNG - Kusrina Kusrina (LPPM STKIP PGRI Bandar Lampung, 2020)
The problem raised in this research is to improve the ability to write poetry of students with an integrated learning approach in learning Indonesian in class V SDN 1 Sukamenanti Kedaton Bandar Lampung Academic Year 2017 / 2018. This research was conducted because of the reality in the field that the ability to write class poetry V in SDN 1 Sukamenanti is classified as low, it is obtained that data in the basic competence of writing poetry the average value of students is 57.39 The average value obtained by these students in general has not reached the specified KKM, which is 65. Of the 28 students in SD Negeri 1 Sukamenanti Bandar Lampung only 10 or 36% of students achieved mastery. The rest, students can achieve completeness after taking remedial once, twice, or even up to three times. This shows that the ability to write poetry of fifth grade students at SD Negeri 1 Sukamenanti Bandar Lampung is low. For this reason, the most integrated learning approach is used in order to improve the ability to write poetry. To achieve the above research objectives, the authors use the